Definition of Spam 2.0: New Spamming Boom - Hayati, Pedram; Potdar, Vidyasagar; Talevski, Alex; Firoozeh, N.; Sarenche, S.; Yeganeh, E. (IEEE, 2010)
The most widely recognized form of spam is e-mail spam, however the term “spam” is used to describe similarabuses in other media and mediums. Spam 2.0 (or Web 2.0 Spam) is refereed to as spam content that is hosted on online Web 2.0 applications. In this paper: we provide a definition of Spam 2.0, identify and explain different entities within Spam 2.0, discuss new difficulties associated with Spam 2.0, outline its significance, and list possible countermeasure. The aim of this paper is to provide the reader with a complete understanding of this new form of spamming.